Three-dimensional architecture design enables hexaazatriphenylene-based polymers as high-voltage, long-lifespan cathodes for aqueous zinc–organic batteries - Lei Li; Siqi Liu; Jie Luo; Xunan Hou; Junhua Kong; Qichong Zhang; Wenyong Lai; Chaobin He (eScience)
Affordable, easily recycled organics with electroactive centers have drawn attention in the pursuit of high-performance aqueous zinc organic batteries (AZOBs). However, intrinsic barriers such as high solubility, undesirable potential, and inferior conductivity hinder their further development. To this end, we have designed an advanced cathode material for AZOBs, comprising an n-type polymer with a three-dimensional (3D) building block (HAT-TP) formed by polymerizing 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexazepenanthrene (HAT-CN) and 3D 2,3,6,7,14,15-hexaaminotriptycene (THA-NH2). The introduction of a 3D architecture not only bolsters the insolubility but also exposes redox-active sites for cation coordination, while the material's extended conjugated system promotes electronic delocalization to increase the redox potential and conductivity. As a result, a HAT-TP battery exhibits a notable initial discharge voltage of 1.32 ​V at 0.1 ​A ​g−1, followed by a midpoint voltage of 1.17 ​V. Remarkably, an ultrastable capacity retention ratio of up to 93.4% is achieved, even after 40,000 cycles at 5 ​A ​g−1. Theoretical simulations reveal that the elevated discharge potential results from the strong electronic delocalization of HAT-TP, which improves the affinity with cations. Ex situ characterizations and theoretical calculations verify that the reversible Zn2+/H+ co-storage mechanism involves only electroactive C=N sites and the best possible coordination paths between them.